Zones of instability : literature, postcolonialism, and the nation - Szeman, Imre, 1968- (Johns Hopkins University Press, 2003)
"In Zones of Instability, Imre Szeman examines the complex relationship between literature and politics by exploring the production of nationalist literature in the former British empire. Taking as his case studies the regions of the British Caribbean, Nigeria, and Canada, Szeman analyzes the work of authors for whom the idea of the "nation" and literature are inexorably entwined, such as Chinua Achebe, Wole Soyinka, C.L.R. James, Frantz Fanon, and V.S. Naipaul. Szeman focuses on literature created in the two decades after World War II, decades in which the future prospects for many newly independent former colonies went from extreme political optimism to often bitter political disappointment. He argues that "nation" can be read as that space in which literature is thought to be able to reunite two things that history has separated - the writer and the people."--Jacket